2012
DOI: 10.1016/j.bbrc.2012.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the human SH3BP2 promoter

Abstract: SH3BP2 activating mutations lead to a unique clinical condition in which patients develop symmetrical bone resorptive lesions of the jaw, a condition termed cherubism. Due to this specific temporal sequence and location of bone resorption, we investigated the transcriptional regulation of SH3BP2 expression. Analyses of 5′- and 3′-serial promoter deletions defined the core promoter/regulatory elements, including two repressor sites (from −1,200 to −1,000 and from +86 to +115, respectively) and two activator sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Although SH3BP2 functions have not been entirely elucidated, plausible interactions of this protein with MAPK/ERK pathway have been raised by others [ 1 ], but such interactions remain untested. The SH3BP2 gene contains C/G‐rich regions and more than 42 CpG islands which are targets for gene regulation by DNA methylation, which likely makes it susceptible to regulation by epigenetic mechanisms [ 35 ]. Interestingly, the DNA methylation analysis shows that cherubism samples cluster together with central GCG, highlighting that the similarities extend from microscopic to the epigenetic level, despite genetic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Although SH3BP2 functions have not been entirely elucidated, plausible interactions of this protein with MAPK/ERK pathway have been raised by others [ 1 ], but such interactions remain untested. The SH3BP2 gene contains C/G‐rich regions and more than 42 CpG islands which are targets for gene regulation by DNA methylation, which likely makes it susceptible to regulation by epigenetic mechanisms [ 35 ]. Interestingly, the DNA methylation analysis shows that cherubism samples cluster together with central GCG, highlighting that the similarities extend from microscopic to the epigenetic level, despite genetic differences.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study demonstrated that knock‐in mice for SH3BP2 would alter bone quality, reduce osteoblast function, and contribute to bone resorption (Wang et al., ), demonstrating the importance of this gene in the osteoclastogenesis. SH3BP2 product was initially identified as a c‐Abl‐binding protein in mice and humans, and despite its presence in most of the human cells, cherubism lesions are intriguingly restricted to the jaws, also carrying a temporal clinical manifestation (Fan et al., ; Reichenberger et al., ). Different mutations affecting SH3BP2 have been described in literature, and all alterations found in this study (R415Q, P418T, and P418H) had already been described before, all of them involving exon 9 (Sangu et al., ; Sekerci et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of PARP1 on bone, SH3BP2 might act as a modifier of PARP1-mediated bone homeostasis, not just tankyrase-mediated bone homeostasis. PARP1 is reported to bind the human SH3BP2 promoter and regulates SH3BP2 gene expression [87]. In PARP1-deficient murine bone marrow-derived macrophages, Sh3bp2 promoter activity and SH3BP2 protein expression are significantly suppressed [87].…”
Section: Effects Of Tankyrase Inhibition On Bonementioning
confidence: 99%
“…PARP1 is reported to bind the human SH3BP2 promoter and regulates SH3BP2 gene expression [87]. In PARP1-deficient murine bone marrow-derived macrophages, Sh3bp2 promoter activity and SH3BP2 protein expression are significantly suppressed [87]. Though further research will be required to determine whether SH3BP2 is involved in PARP1-mediated bone homeostasis, SH3BP2 might be involved in osteoclast differentiation through two different mechanisms, transcriptional regulation by PARP1 and post-translational regulation by tankyrase.…”
Section: Effects Of Tankyrase Inhibition On Bonementioning
confidence: 99%